2020
DOI: 10.1055/s-0040-1716312
|View full text |Cite
|
Sign up to set email alerts
|

The Retromolar Space and Wisdom Teeth in Humans: Reasons for Surgical Tooth Extraction

Abstract: Objective This article explores the problem of developing pathologies in the retromolar region. Findings can serve a framework for disease prevention and for the improvement of the quality of life of patients. The present study aims to justify the possibility of utilizing morphometric methods to foresee problems in the eruption of third molars. Materials and Methods A comprehensive morphometric study of the lower jaw and facial skeleton involves 100 skulls of Homo sapiens to identify the anatomical causes of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…24 25 CBCT has been extensively used to study the axial inclination, spatial orientation, and relation of the mandibular third molar to the inferior alveolar nerve canal. 26 27 28 29 Similarly, CBCT can also be used to evaluate maxillary sinus and help detect any septae or other pathology that can alter the dentoalveolar treatment planning. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 25 CBCT has been extensively used to study the axial inclination, spatial orientation, and relation of the mandibular third molar to the inferior alveolar nerve canal. 26 27 28 29 Similarly, CBCT can also be used to evaluate maxillary sinus and help detect any septae or other pathology that can alter the dentoalveolar treatment planning. 30…”
Section: Discussionmentioning
confidence: 99%
“…24,25 CBCT has been extensively used to study the axial inclination, spatial orientation, and relation of the mandibular third molar to the inferior alveolar nerve canal. [26][27][28][29] Similarly, CBCT can also be used to evaluate maxillary sinus and help detect any septae or other pathology that can alter the dentoalveolar treatment planning. 30 Jung and Cho suggested that a maxillary sinus floor superimposition on the teeth root on a panoramic radiograph should be further probed to predict the chances of sinus floor perforation.…”
Section: Discussionmentioning
confidence: 99%